MeshAdmin: uma plataforma integrada para gerência de redes em malha sem fio - Valle, Rafael de Tommaso do (2011)
Wireless mesh networks (WMNs) are emerging as a low-cost alternative for wideband access. Those networks are composed by wireless routers and clients using the IEEE 802.11 standard in ad-hoc mode. WMNs provide a wireless backbone where information is transmitted using the wireless links through multihop communication. There are several techniques and tools proposed in the literature for wireless mesh network management. Each of those techniques and tools usually includes just a few functionalities leading to the use of more than one together. This work discusses a set of requirements of an integrated platform for wireless mesh network management. This work also presents MeshAdmin, a management platform that fulfills a subset of the presented requirements. In order to evaluate MeshAdmin monitoring traffic overhead and its capability of detecting network faults, experiments done in a real mesh testbed are presented.